Characteristic Design Of Keris Pandai Saras - Nurulliyana , Norman; Rafeah , Legino; Norwani , Md. Nawawi (2014)
Keris Pandai Saras is one of the distinctive weapon heritage in Malaysia. The past comprehensive study about Keris have written much regarding its method of manufacture; the customs; and the traditions of its origin, which learn by Malay from Javanese sources.Therefore, this paper is an attempt to throw some light on the characteristic design of Keris Pandai Saras that will differentiate their design with other types of Keris in Malaysia.In this study, overview and review through literature, which provides images is useful as to determine the common design for Keris compare to the Keris Pandai Saras. However, the interview with the expert manufactured of Keris will be conducted. As well as observed and captured selected several samples the Keris Pandai Saras will analysed their design features. The findings of this research is different design Keris are accoding their ganja in blade. Thecharacteristic of design Keris Pandai Saras according their aring or ganja which is Kerawang andAkut or Belalai Gajah. All this characteristic must be have to find the design Keris Pandai Saras. From this research, people can know the chacteristic of design Keris Pandai Saras and the different of other Keris in Malaysia. This research only focuses on one of the Keris in Malaysia which is Keris Pandai Saras.The finding is very useful to emphasize the importance of Keris Pandai Sarasand sustaining the Malay heritage in Malaysia